Technology of Processing into Refined Grains - Askarova Khurshida Ekram kizi (Scientific Trends, 2024)
The article describes the properties of separating grain mixtures in different types of separators. In the grain processing industry, digitization allows the development of mathematical models of queue sorting systems. Algorithms for analyzing the physical properties of the grain mass have been developed. The study of wheat processing products is based on the analysis of ground grain using computer vision techniques and artificial neural networks developed by software tools. The classification of grain according to the geometric properties of Mill particles makes it possible to predict the technological characteristics of Wheat Quality, in particular the indicator of its hardness, with high accuracy (the evaluation error does not exceed 3.7%).
Keywords: Grain, wheat, grain processing.